The Concept of Quadruple Helix Collaboration and Quintuple Helix Innovation as Solutions for Post Covid 19 Economic Recovery - Rahma Wahdiniwaty; Deri Firmansyah; Dede Dede; Asep Suryana; Asep Achmad Rifa'i (Universitas Mercu Buana, 2022)
The COVID-19 pandemic has had a serious impact on the health, economy, transportation, and other industrial crises. The implementation of the lockdown or PSBB has disrupted the operations of various economic sectors.Objectives: The purpose of this research is to describe the concept of the Quadruple Helix collaboration and the Quintuple Helix Innovation model as part of the collaboration, innovation, and synergy initiatives between multi actors to help find solutions in an effort to recover the national economy after COVID-19 in implementing government policies.Methodology: The research method used is the descriptive qualitative method using secondary data from various works of literature, such as books, articles, and home pages to access information data relevant to the Quadruple Helix collaboration concept, namely government, academia, company, and society. The analysis technique was carried out by descriptive analysis.Finding: Based on the research results, it can be seen that the Quadruple Helix collaboration concept is a solution for national economic recovery which can refer to the structure, process, input, and output.Conclusion: The Quintuple Helix Innovation model views more comprehensively the importance of adaptability and the suitability of interactions with social environmental conditions in every process from the structure, the process itself, input and output along with its evaluation.